Play It Again Sam: The Poetics of Narrative Repetition in 1 Samuel 1-7 - Firth, David G. (Tyndale bulletin, 2005)
A final form reading of 1 Samuel 1–7 is offered here, examining the narrative poetics of repetition and its relationship to complete and incomplete elements of plot. Five key repetitions are examined – monarchy, the authentic prophetic word, the fall of the house of Eli, YHWH’s independent reign and prefiguring allusions to Saul. Although the text undoubtedly makes use of sources, it is argued that it is considerably more than their sum as these elements are woven together into a coherent whole in a manner that prepares the reader for the issues that are to be addressed in subsequent narratives. In particular, the conflicts that surface in chapters 8–12 are seen to be within the frame of YHWH’s intentions since they are anticipated in these chapters. As with any good introduction, the reader is left waiting to see how it will develop.